Stimulation effect of electric current density (ECD) on microbial community of a three dimensional particle electrode coupled with biological aerated filter reactor (TDE-BAF). (November 2017) - Feng, Yan; Li, Xing; Song, Ting; Yu, Yanzhen; Qi, Jingyao
Highlights: TDE-BAFs were applied to treat municipal wastewater. ECD of 14.25 A·m −2 exhibited the highest CODcr, TOC and NH4 + -N average removal rates. High ECD, exceeding 14.25 A·m −2, inhibit the growth and activity of bacterium. Microbial communities and physicochemical properties explained removal performance. The ECD is the key parameter affecting the removal efficient. Abstract: Improving the stimulation effect of electric current density (ECD) on microbial community is critical in designing and operating TDE-BAF. This study investigated the effect of ECD at 0.00, 4.08, 6.12, 12.20, 14.25, 16.30 and 20.20 A·m −2 on the removal performance, diversity and structure of microbial community in TDE-BAF. Results indicated that the ECD of 14.25 A·m −2 exhibited the highest COD, TOC and NH4 + -N average removal rates with 93.33%, 91.26% and 93.87%, respectively; Under high ECD, especially exceeding 14.25 A·m −2, the inhibition of growth and activity because of plasmatorrhexis was in agreement with the sharp biomass decline; there was no significant relation between community richness and diversity and removal efficiency below optimum ECD, while above optimal ECD, it was just the opposite; Microbial communities mainly including Hydrogenophaga, Saprospiraceae_uncultured, Delftia, Enterobacter, Pseudomonas, Pseudoxanthomonas, and Nitrosospira and physicochemical properties well explained the excellent removal performance at the optimum ECD.